Utilization of Instructional Materials and Junior Secondary Students’ Academic Achievement in Geometrical-Shapes - Ahmad, Manko Umar; Aliyu, Alhaji Zakariyya; Liman, Alhaji Mohammed (Brillo Journal, 2024)
This study investigates the utilization of instructional materials and junior secondary students’ academic achievement in geometrical shapes. A quasi-experimental design with experimental and control groups, including pre-test, post-test, and post-posttest measures, was implemented. The target population consisted of 1329 JSS II Students from Bida Local Government Area, Niger State, with sample size of 171 (Male=84, Female=87) students from two schools and two intact classes. Sample was determined through purposive and simple random sampling, selecting all mixed schools with experimental and control groups. Three research questions and hypotheses were formulated to guide the study. Data collected employed instruments: The Geometry Performance Test (GPT), Geometry Achievement Test (GAT), Lesson model for the control and experimental group. The GPT and GAT were validated by three experts and also demonstrated good reliability. The results revealed that students taught with instructional material performed better comparing with those taught without instructional materials and also there is no significant differences found in gender in the experiment group. In addition, there is significant difference in the retention ability of those who were taught using instructional materials and those taught without instructional material. Based on these results, mathematics teachers should use instructional materials during teach mathematics especially geometrical shapes.